The role of recreational physical activity in developing the psychosocial adjustment of people with physical disabilities who practice adapted physical activity - Sedira, saad (sports creativity, 2025)
Undoubtedly, when individuals with special needs experience emotions such as fear, sadness, and anger as a result of their disability, these emotions are accompanied by serious physical changes or disturbances. Physical development is influenced by psychological development, as there is a close connection between mind and body; the mind affects the body, and the body affects the mind.